Formation of Transversal Competencies in the Process of Future Primary School Teachers’ Training - Matvienko, Olena; Popova, Liudmyla (Journal of Vasyl Stefanyk Precarpathian National University, 2022)
. The article updates the problem of professional training of future primary school teachers in the context of forming the necessary knowledge, skills and abilities. Different views of scientists on the content of the concepts of competency, competence and professional competency of pedagogical workers are considered. Ways of forming transversal competencies in the process of training future primary school teachers, the modern form of development of professional knowledge and communication, which in fact determines the urgency of finding optimal ways and means of its implementation at the current stage, are considered. The lack of systematic scientific and methodological support determines the relevance of the study of transversal competences in the preparation of future primary school teachers in the modern system of international educational professional training. An attempt was made to analyze the main trends of reforming professional education in the European educational space (Romania, Bulgaria, Ireland, Finland, Portugal, etc.). It also actualizes the need to study and use the experience of foreign countries, taking into account the specifics of domestic realities, and to make a comparative analysis of the theory, methodology and organization of future primary school teachers training in the context of modernization of the education system in Ukraine.